Web Site Recommendation Modelling Assisted by Ontologies Networks - Rohrer, Edelweis; Motz, Regina; Díaz, Alicia (Cadernos de Informática, 2010)
Web site recommendation systems help to get high quality information. The modeling of recommendation system involves the combination of many features:metrics of quality, quality criteria, recommendation criteria, user profile, specific domain, among others. At the moment of the specification of a recommendation system it must be guaranteed a right interrelation of all of this features. In this paper we propose a ontology network based process for web site recommendation modeling. This ontology network conceptualizes the different domains (web site domain, quality assurance domain, user context domain, recommendation criteria domain, specific domain) in a set of interrelated ontologies. Basically, this work introduces the semantic relationships that were used to construct this ontology network. Moreover, it shows the usefulness of this ontology network for the detection of possible inconsistencies when specifying recommendation criteria. Particularly, this approach is illustrated for the health domain.